Analisis Faktor-Faktor Penyebab Kurangnya Pemahaman Masyarakat Tentang Asuransi di Indonesia - Yulia Febrianti; Zainarti Zainarti (Journal of Islamic Economics and Finance, 2025)
The purpose of this study is to examine the elements that contribute to the Indonesian population's poor insurance knowledge. Even though insurance plays a significant role in offering financial security, public involvement is still minimal. This study highlights a number of important elements, such as a strong sense of communal solidarity, limitations in commercial communication, and inadequate financial literacy. People often rely on unofficial social assistance, which makes them believe that insurance is not necessary. Misunderstandings about the advantages of insurance are also a result of insurance firms' poor marketing strategies and lack of socialization. Data was gathered from a variety of pertinent literature sources using a literature review and qualitative analysis process. The results show that more successful teaching approaches that are appropriate for the local cultural context are required to improve public awareness and involvement in insurance. It is anticipated that this research will aid in the creation of programs and policies that will raise insurance literacy in Indonesia.